(untitled) (Journal of Engineering, 2003)
This paper presents the development of a flexible, modular, and cost-effective PC-Based CNC machine controller. Software is designed and developed to perform most of the standard CNC machines control functions. This software is capable of accepting and inteqpreting the standard CNC (G-Code) programs. [t also performs the most important CNC machine controller functions; namely, interpolation and feed rate control. The software has been developed using the Visual C++ programming language operating under WINDOWS environment. It has high flexibility and expandability that makes the task of future development easier. System perfonnance has been evaluated by applying the developed software to control an X-Y recorder,simulating a CNC machine.